Bedaquiline Resistance: Its Emergence, Mechanism, and Prevention - Nguyen, Thi Van Anh; Anthony, Richard M; Bañuls, Anne-Laure; Nguyen, Thi Van Anh; Vu, Dinh Hoa; Alffenaar, Jan-Willem C (Clinical infectious diseases, 2018)
Bedaquiline, a new antituberculosis drug, has already been used in >50 countries. The emergence of bedaquiline resistance is alarming, as it may result in the rapid loss of this new drug. This article aims to review currently identified mechanisms of resistance and the emergence of bedaquiline resistance, and discuss strategies to delay the resistance acquisition. In vitro and clinical studies as well as reports from compassionate use have identified the threat of bedaquiline resistance and cross-resistance with clofazimine, emphasizing the crucial need for the systematic surveillance of resistance. Currently known mechanisms of resistance include mutations within the atpE, Rv0678, and pepQ genes. The development of standardized drug susceptibility testing (DST) for bedaquiline is urgently needed. Understanding any target and non-target-based mechanisms is essential to minimize resistance development and treatment failure and help to develop appropriate DST for bedaquiline and genetic-based resistance screening.